Material resource utilization, a correlate of students' performance in secondary school physics in Oyo State (2000)
The aim of this paper is to examine the relationship between the material resource utilization and students' performance in secondary school physics in Oyo State. Material resources vary from students' own items like students chairs and lockers to such materials owned by schools like school bus. In other words, material resources are those things used in schools to facilitate teaching and learning processes. A total of 1029 SS1 Physics students from 40 schools with their principal participated in the study. Descriptive statistics and multiple regression analysis were used to answer the research questions 1 and 2 respectively. Two research instruments were used in this study. These include Physics Achievement Test (PAT) and the School Questionnnaire (SQ). The results of the study shows that the level of the material resources in Oyo State Secondary School is low. Material resources such as textbooks, library size, fan, students' stools in the laboratory are found to significantly predict students' performance in secondary school Physics in Oyo State. It is therefore, recommended that more of these material resources should be provided in the schools.